Diabetic microvascular complications as simple indicators of risk for cardiovascular outcomes and heart failure - Preiss, D; Sattar, N (Lancet, 2016)
Occasionally a paper comes along which, while reinforcing established wisdom, does so in a manner which is potentially clinically impactful. In The Lancet Diabetes and Endocrinology, Jack Brownrigg and colleagues1 take advantage of the excellent Clinical Practice Research Datalink (CPRD) to examine the associations of microvascular complications with cardiovascular risk, admission to hospital for heart failure, and all-cause mortality in patients with type 2 diabetes. Its simple message is that the presence of any microvascular disease independently signals risk for cardiovascular disease (peripheral neuropathy, hazard ratio [HR] 1·40 [95% CI 1·19–1·66]; retinopathy, HR 1·39 [1·09–1·76]; nephropathy, HR 1·35 [1·15–1·58]), sufficient to warrant robust preventive therapy.